ANALISIS KARAKTERISTIK LALU LINTAS TERHADAP TINGKAT PELAYANAN PADA RUAS JALAN JENDERAL GATOT SUBROTO KABUPATEN PACITAN - Rajasa, Gnemon Isvandianto Surya; Prasetyawati, Erlina; Rifai, Muhammad Abdul; Prawoto, Prawoto (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
This research aims to analyze traffic characteristics and their impact on the level ofservice on Jalan Jenderal Gatot Subroto in Pacitan Regency. This road section isone of the important arteries that connects various areas in Pacitan Regency, andhas a big influence on mobility and the local economy. The research methodinvolves collecting traffic data through direct observation, traffic volume surveys,and measuring vehicle speeds during peak and off-peak hours. The collected datawas analyzed using road capacity analysis methods and traffic simulation models toassess the level of service (LOS) on the road section. The results of the researchshow that the characteristic pattern of Jalan Gatot Subroto, vehicle volume isdominated by motorbikes on holidays or weekends with a maximum volume of200.06 cur/hour with a maximum average speed of 31.52 cur/hour at monitoringpoint 2 which is in front of the Bus Terminal. Pacitan with the level of serviceadapted to Jalan Jenderal Gatot Subroto Pacitan from the four points surveyed was2.35, which was obtained at point 2 with a service level of D with a flow dominatedby motorbikes towards the beach tourist attraction at a stable and tolerable speed.These findings provide important insights for traffic planning and management, aswell as recommendations for infrastructure improvements to increase trafficefficiency and safety in the region.